1996
DOI: 10.1002/anie.199602121
|View full text |Cite
|
Sign up to set email alerts
|

Model Compounds for the Homogeneous Hydrodesulfurization of Benzothiophene: Insertion of Manganese into the SC(aryl) Bond

Abstract: The great importance of heterogeneous hydrodesulfurization (HDS)"] has spawned numerous studies with homogeneous model systems.I2] Of particular interest has been the activation of derivatives of thiophene (T), benzothiophene (BT), and dibenzothiophene (DBT). While all three of these sulfur-containing molecules are relevant to HDS, the latter two are especially so because they are more difficult to desulfurize and thus are much more abundant in fossil fuels. The key step in HDS is cleavage of the S-C bonds, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Interestingly, the initial product 15, which is stable if R H, derives from insertion into the C(aryl) ± S bond in BT. Our studies are suggestive [14,17,18] of a radical mechanism, which may be relevant to electron transfer processes thought to occur in HDS. The isomerization 15 3 16 occurs over several hours for R Me via reductive elimination to h 1 -S bonded Mn(CO) 4 followed by oxidative addition.…”
Section: à S and C à O Bond Activationmentioning
confidence: 52%
See 1 more Smart Citation
“…Interestingly, the initial product 15, which is stable if R H, derives from insertion into the C(aryl) ± S bond in BT. Our studies are suggestive [14,17,18] of a radical mechanism, which may be relevant to electron transfer processes thought to occur in HDS. The isomerization 15 3 16 occurs over several hours for R Me via reductive elimination to h 1 -S bonded Mn(CO) 4 followed by oxidative addition.…”
Section: à S and C à O Bond Activationmentioning
confidence: 52%
“…[13] We began work in this field by asking if precoordination of a metal to a carbocyclic ring in BT or DBT would promote the remote activation of the C À S bonds in the adjacent thiophenic ring. [14] To our delight, it was found that this type of precoordination can indeed result in hitherto unseen levels of activation regarding C À S bond cleavage by nucleophiles or by electrons.…”
Section: à S and C à O Bond Activationmentioning
confidence: 96%
“…This general idea of remote activation was previously shown [5] to be highly successful for benzothiophene and analogues. The success with benzofuran suggests that a similar strategy may be applicable to indole derivatives for modeling HDN reactions, and studies to probe this are underway.…”
mentioning
confidence: 97%
“…[2] For these reasons, there has been substantial interest in developing homogeneous model systems for CÀX bond cleavage (X S, N, O) and subsequent removal of the X atom in unsaturated heterocycles. [3,4] We have shown [5] that precoordination of a metal center to the carbocyclic ring of benzothiophene (BT, 1) and dibenzothiophene activates a C À S bond towards cleavage by reducing agents and by metal nucleophiles. The major initial product (n Ä CO 2062, 1998 cm À1 ) in the reaction of 5 also could not be isolated, but 1 H and 31 P NMR data strongly suggest that it is the simple h 2 -olefin complex 7, which results from ethylene displacement by the CÀC double bond of benzofuran.…”
mentioning
confidence: 99%
See 1 more Smart Citation